ANALISIS USAHA BUDIDAYA PEPAYA POLA AGROFORESTRI JATI-PEPAYA DI DESA PURWAHARJA, BANJAR - Yonky Indrajaya; Ary Widiyanto (Jurnal Agroforestri Indonesia, 2019)
The utilization of land under tree stand in teak forest has been widely applied by Perhutani as a means to maintain the quality of teak tree and to give additional income to people living around the teak plantation. In general, the utilization of land under tree stand is by planting crops for limited duration. One of the crops planted under teak stands is papaya that is planted together with teak seedlings until 2 years. This study aims to analyze the feasibility of papaya cultivation under teak stands in Purwaharja Village, Banjar City. The analysis tools used include NPV (Net Present Value) and BCR (Benefit Cost Ratio). The results of this study show that the papaya cultivation under teak stands give NPV of IDR 20,072,606.- and BCR of 2.89. Therefore, the cultivation of papaya under teak stand is feasible to conduct.